The sale and shipment of coal - Callaghan, Hugh Leland John (Institute of Marine and Environmental Law, 2023)
The Coal Industry in South Africa exported 54,5 million tons in 1993, providing R4,2 billion in export revenues, second only to gold. Apart from small parcels of coal exported through Durban and Maputo, coal is exported through the Richards Bay Coal Terminal. As new producers such as Indonesia, Columbia and China enters the International Market, equally (and sometimes better) placed than South Africa to penetrate markets in Europe and the Far East, the South African Coal Industry cannot afford to damage its' competitive position through accusations of "hot coal" problems. In this thesis, the phenomenon of spontaneous healing, combustion and methane emission from coal cargoes, will be discussed, and the F.O.B. sales of coal will be commented upon.